THE MIGHT OF RUSSIAN LANGUAGE ACCORDING TO SYNONYMIC DICTIONARY BY COMPUTER EVALUATION SYSTEM ASIS® - Vitaly N. Trishin (Статистика и экономика, 2016)
The article describes electronic dictionary of synonyms in Russian language by ASIS® system (more than 500 000 words and collocations, 190 000 synonymic connections).The program can be used not just as a dictionary of synonyms and close meaning words, but also as spelling dictionary and definition dictionary of Russian language in order to check the orthography and define the meaning of unknown words. The dictionary is also designed to be an instrument of philological surveys and studies of the language trough the extensive query system on different characteristic of words (definition, composition, synonymy, etc.). Program’s lexical base includes words from dictionaries and guides in all subject areas - from astronomy to Japanese painting. Over compilation of dictionary developer used published dictionaries: spelling, synonymic, definition dictionaries, dictionary of collocations, dictionary of foreign words and etc. of 19-21 cc. Newspapers, magazines and web-resources were active used as well for appending the dictionary. This dictionary practically shows, that by the amount of words Russian language belongs with the most developed languages in the world, and by the scale and density of synonymic space, in the author’s opinion, it has no equal.